Academic procrastination and its relationship with parenting styles and self-esteem among undergraduate students - Lee, Mei Yun (2013)
The purpose of this study is to investigate the issue of academic procrastination and its relationships with parenting styles and the level of self-esteem among undergraduate students. The student’s self-esteem level has been hypothesized as a mediator in explaining the relations between different parenting styles and academic procrastination. A structural model has been proposed in this study to examine the mediating function of self-esteem on the relations between different parenting styles and student’s involvement in academic procrastination. In this study, a sample of 376 undergraduate students (204 males, 172 females) between the ages of 19 and 23 years old completed measures of Procrastination Assessment Scale - Students (PASS), Parental Authority Questionnaire (PAQ) and Rosenberg Self-Esteem Scale (RSES). The results revealed that there were significant correlations between three different parenting styles and academic procrastination among undergraduate students. Furthermore, results of multiple regression analyses showed that self-esteem level acts as a partial mediator in the relations between different parenting styles and academic procrastination. Besides, the results also found that there was a gender difference between male and female students in academic procrastination. Several implications and recommendations for further research are discussed in this study.